A Retrospective Study of Gemcitabine and Carboplatin With or Without Intravenous Vitamin C on Patients With Advanced Triple-Negative Breast Cancer. (February 2020) - Ou, Junwen; Zhu, Xinyu; Zhang, Hongyu; Du, Yanping; Chen, Pengfei; Wang, Junhua; Peng, Xiufan; Bao, Shuang; Zhang, Xinting; Zhang, Tao; Pang, Clifford L. K.
Background: This is a retrospective study to examine the effect of chemotherapy with or without intravenous vitamin C (IVC) on women with advanced triple-negative breast cancer (TNBC).Methods: From 2008 to 2016, a total of 113 patients with pathologically confirmed TNBC at Clifford Hospital were evaluated, and 70 patients were matched and divided into IVC (treatment group) and non-IVC groups (control group). The match was according to age, menopausal status, and metastatic sites. In the control group, 35 patients received gemcitabine and carboplatin. In the treatment group, 35 patients received the same chemotherapy plus IVC.Results: Baseline characteristics were not significantly different between the 2 groups. According to the criteria of RECIST 1.1 (Response Evaluation Criteria in Solid Tumors), enhanced computed tomography scan was compared after 2 cycles of chemotherapy. In the treatment group, 2/35 cases had a complete remission (CR), 15/35 cases had partial remission (PR), and 13/35 cases had stable disease (SD). The response rate was 48.6%. In the control group, there were no CR cases, 14/35 cases had PR, 14/35 cases had SD, and the response rate was 40.0% ( P > .05). The median progression-free survival time and median overall survival time was 7 months (95% confidence interval [CI] =1.5-28.5 months) and 27 months (95% CI = 4-40 months) in the treatment group compared with 4.5 months (95% CI = 1.5-8 months) and 18 months (95% CI = 3-26 months) in the control group ( P < .05). All patients experienced diverse reactions in the gastrointestinal tract and myelosuppression. The incidence of adverse reactions in the treatment group was significantly lower than that of the control group ( P < .05).Conclusion: IVC may have an effect on improving the prognosis of patients with advanced TNBC.